RIMS: A new approach to measuring firm internationalization - Marshall, Victor B; Brouthers, Lance Eliot; Keig, Dawn L (Journal of International Business Studies, 2020)
Understanding the antecedents to, and consequences of, a firm’s degree of internationalization is integral to international business research. In order to be accepted by scholars, empirical research that tests hypotheses regarding drivers and/or consequences of firm internationalization needs to use a valid measure of firm internationalization. In this paper, we develop a new measure, the ratio of international market shares (RIMS); RIMS measures a firm’s degree of conformance to the theoretically grounded characteristics of a maximally internationalized global firm. RIMS is theoretically and empirically compared to three widely used measures of firm internationalization: foreign sales to total sales (FSTS), international diversification, and international scope. Each of the three is shown to have serious limitations while RIMS does not. In addition to being theoretically based, RIMS also has the advantages that it: measures the degree to which a firm has penetrated the rest of the world’s market relative to the degree it has penetrated its primary market; captures the combined effects of the breadth and average depth of internationalization; is easy to calculate; is easy to interpret, and is calculable for more firms than measures of diversification or FSTS. All four measures are tested on a sample of large manufacturing firms.